2018
DOI: 10.1002/term.2615
|View full text |Cite
|
Sign up to set email alerts
|

Human dental stem cell derived transgene‐free iPSCs generate functional neurons via embryoid body‐mediated and direct induction methods

Abstract: Induced pluripotent stem cells (iPSCs) give rise to neural stem/progenitor cells, serving as a good source for neural regeneration. Here, we established transgene-free (TF) iPSCs from dental stem cells (DSCs) and determined their capacity to differentiate into functional neurons in vitro. Generated TF iPSCs from stem cells of apical papilla and dental pulp stem cells underwent two methods-embryoid body-mediated and direct induction, to guide TF-DSC iPSCs along with H9 or H9 Syn-GFP (human embryonic stem cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
0
16
2
Order By: Relevance
“…In conclusion, this study demonstrates a simple and efficient method to develop EBs from oral cavity derived stem cells, according to the study showing that DPSCs are able to form embryoid-body-like structures in vitro containing cells derived from all three embryonic germ layers when injected in nude mice ( Yan et al, 2010 ). Moreover, it has been demonstrated that oral derived stem cells possess higher reprogramming efficiency than dermal fibroblasts, thus prove that these cells are more amenable for reprogramming ( Pisal et al, 2018 ) and that transgene-free-DSC iPSCs are capable to undergo toward neurogenic differentiation till to functional neurons stage in vitro ( El Ayachi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study demonstrates a simple and efficient method to develop EBs from oral cavity derived stem cells, according to the study showing that DPSCs are able to form embryoid-body-like structures in vitro containing cells derived from all three embryonic germ layers when injected in nude mice ( Yan et al, 2010 ). Moreover, it has been demonstrated that oral derived stem cells possess higher reprogramming efficiency than dermal fibroblasts, thus prove that these cells are more amenable for reprogramming ( Pisal et al, 2018 ) and that transgene-free-DSC iPSCs are capable to undergo toward neurogenic differentiation till to functional neurons stage in vitro ( El Ayachi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…When cultured in neuronal inductive conditions for an extended period of time, DPSCs exhibit a neuronal morphology and express neuronal-specific markers such as PSA-NCAM, β -III tubulin, neurofilament-M, and nestin, showing the ability to generate a sodium current consistent with functional neuronal cells [ 70 ]. Moreover, DPSCs transplanted in vitro can generate functional neurons and improve nerve regeneration [ 71 , 72 ]. In addition, several studies also showed that DPSCs exhibit the capacity to acquire the phenotype of endothelial cells and generate vascular-like structures [ 73 76 ].…”
Section: Dpscsmentioning
confidence: 99%
“…These OSCs are heterogeneous population of cells expressing typical MSC markers 13,15 . The above mentioned isolation method routinely gives rise to clonogenic MSCs capable of expansion with robust proliferation in cultures [23][24][25][26] . The size and morphology of DPSCs and SCAP in subconfluent cultures were very similar.…”
Section: Cell Culturementioning
confidence: 99%
“…The staining followed a protocol reported previously 23,26,29 , or with modified approaches as follows. Cell cultures were fixed in 100% ice cold methanol for 10 min, followed by permeabilization with 0.1% Triton-X 100 (Sigma-Aldrich) in PBS for 15 min at room temperature.…”
Section: Immunocytofluorescence Stainingmentioning
confidence: 99%